GLOBAL CAPITALISM AND THE RISE OF PRIVATE EQUITY AND OUTSOURCING - Callender, Guy (The journal of contemporary issues in business and government, 2007)
The popularity of contracting out or outsourcing has remained undiminished in both public and private sectors as organisations seek to satisfy their many stakeholders that they function in an efficient and cost effective manner. The rise of contracting out can be attributed to the ideological support for contracting out provoked by the free market economic policies popularised in the 1980s, universal pressure on costs, and the encouragement of authors as diverse as Peters and Waterman (1982) and Friedman (2005). An emerging funding source for both public and private sectors is private equity capital. Once associated with high risk ventures but now financing mainstream corporate activities, the rise of private equity has been sudden. This paper draws together the combined themes of contracting out and private equity with particular emphasis on the lack of financial performance and transparency created by each, and their potential impact on competitive markets and global capitalism?